A budapesti hajléktalanok számának becslése - Dávid, Beáta; Snijders, Tom (Szociológiai Szemle, 2024)
In this paper we try to estimate the size of the homeless population in Budapest by using two - non-standard - sampling methods: snowball sampling and the capture-recapture method. Using two methods and three different data sets we are able to compare the methods, the results and also suggest some further applications. Apart from the practical purpose of our study there is a methodological one as well: to use two relatively unknown methods for the estimation of this very peculiar kind of population.